General public awareness, knowledge, and beliefs toward palliative care in a Saudi population - Hasan Mohammed Alkhudairi (Wolters Kluwer Medknow Publications, 2019)
Objectives: Public awareness of palliative care (PC) is satisfactory in only twenty countries in 2013, which does not include Saudi Arabia in spite of the global efforts done to enhance the public awareness of PC. This study was conducted to evaluate the awareness, knowledge, and beliefs of the Saudi adult population about PC. Methods: A cross-sectional design study was conducted in December 2017 using a self-administered questionnaire survey that was sent through Google Docs to assess the Saudi general public on the awareness of PC. Results: There were 1987 (out of 3164, 62.8% response rate) Saudi adults who responded to the survey, in which 60.3% were males (mean age: 39.50 years, median: 39.0 years, and range: 15-77 years). There were 321 (16.2%) respondents who reported that they know PC and 454 (22.8%) answered that they have heard or were aware of PC. A total of 755 (38.2%) believe that PC improves the quality of life of sick people and 684 (34.4%) believe that PC can reduce the physical suffering of patients. Knowledge of PC was not statistically significantly affected by gender, place of residence, and marital status. On the other hand, employment and having higher levels of education led to better knowledge and more awareness of PC. Conclusion: The current study demonstrated that the knowledge and awareness of PC is still low among surveyed Saudis. There is a need for the government to advocate institutions to functionally devote programs and initiatives and promote literacy of PC in the general population. Nongovernmental sectors should also participate in programs to improve the knowledge and awareness of PC.